Viability, Migration Rate, and mRNA Expression of GLUT5, GLUT7, GLUT11 in WiDr Colorectal Cancer Cell Line - Nurul Hidayah; Ika Yustisia; Rosdiana Natzir; Lia Hafiyani; Ilhamuddin Ilhamuddin; Hijral Aswad; Marhaen Hardjo (The Prodia Education and Research Institute (PERI), 2023)
BACKGROUND: Insufficient glucose levels in colorectal cancer (CRC) patients leads to a condition where fructose might become an alternative source for cells proliferation, but the role of fructose or fructose-glucose combinations in development of CRC has not been elucidated well. In this study, the effect of fructose-glucose variations on viability, migration, and glucose transporter (GLUT)5, GLUT7, GLUT11 mRNA expressions in WiDr CRC cell line were examined.METHODS: Cells were treated with varying ratios of fructose-glucose (F100%; F75%:G25%; F50%:G50%; F25%:G75%; G100%; F: Fructose, G: Glucose). Untreated cells (F0:G0) were used as cell control. The 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyl-2H-tetrazolium bromide (MTT) assay was used for cell viability test, scratch assay was used to examine the cell migration, and quantitative polymerase chain reaction (qPCR) was performed to examine mRNA expressions. Data were analyzed using one-way analysis of variance (ANOVA) and followed with Tukey's post-hoc test, with p<0.05 consideres as significant.RESULTS: Fructose-glucose combinations and glucose 100% significantly increased the cell viability compared to control (p<0.05). All treatment groups showed a significant increase in cell migration compared to control (p=0.000). Only GLUT7 and GLUT11 expressions in the G100% group were significantly different compared to the control (p=0.000). GLUT7 and GLUT11 expressions were also significantly different in F100% and F50%:G50% treatments compared to G100% (p=0.000).CONCLUSION: Taken together, fructose might play important role in cell migration. However, in cell viability, combination with glucose could increase fructose's effect. Fructose might not affect the mRNA expressions of GLUT5, GLUT7 and GLUT11.KEYWORDS: GLUT5, GLUT7, GLUT11, fructose transporter, colorectal cancer, WiDr